Enhancing the Reading Comprehension of Students in Narrative Text Using Story Face Strategy - Syah, Albian; Saputra, Joni (Universitas Veteran Bangun Nusantara, 2020)
This study was a Classroom Action Research that deals with story face strategy’s use to enhance the students’ reading comprehension of narrative text. The purpose of this study was to reveal the execution of story face strategy in the process of narrative text teaching and learning, and also to describe about reading comprehension of after using story face strategy in classroom. The participants were all students of grade X.2 grade of Miftahul Huda Sungai Luar. The instruments to collect qualitative data were observation sheet, interview, and field note. The quantitative instrument is reading comprehension test. On the basis of data analysis, it is found that Story Face Strategy enhanced students 'understanding of reading in narrative text. The improvements occurred in cycle 1 and cycle 2. The improvement of students’ reading comprehension is 59.4 (enough) to 71.7 (good). The result suggests that the use of the story face strategy to enhance students 'understanding of reading in narrative text is successful for grade X.2 students. The variables that alter the enhancement of the students depending on the results of the interview and observation indicate students' enthusiasm when using of story face sheets in the story face strategy.